Lower resting cardiac autonomic balance in young adults with current major depression. (25th April 2019) - Brush, Christopher J.; Olson, Ryan L.; Ehmann, Peter J.; Bocchine, Anthony J.; Bates, Marsha E.; Buckman, Jennifer F.; Leyro, Teresa M.; Alderman, Brandon L.
Abstract: Research on cardiac autonomic function in major depressive disorder (MDD) has predominantly examined cardiac vagal control and adopted a model of reciprocal autonomic balance. A proposed bivariate autonomic continuum uses cardiac autonomic balance (CAB) and cardiac autonomic regulation (CAR) models, derived from normalized values of respiratory sinus arrhythmia and pre‐ejection period, to more adequately index patterns of autonomic control. The purpose of this study was to assess resting levels of CAB and CAR among young adults with and without a current diagnosis of major depression. One hundred forty‐two young adults ( n = 65 MDD, n = 77 healthy controls; 20.8 ± 2.6 years) completed a structured diagnostic interview, cardiovascular assessment, and a maximal aerobic fitness test. The findings revealed that CAB, but not CAR, significantly predicted current MDD status ( OR = 0.70, 95% CI [0.53, 0.93]), an effect that remained after controlling for aerobic fitness and body mass index. Although CAB was found to be a significant predictor of current MDD status among a sample of young adults, there remained substantial variation in autonomic control that was not captured by the traditional model of reciprocal autonomic balance. Abstract : Major depressive disorder (MDD) is characterized by disrupted autonomic function; however, previous research has focused mainly on deficits in parasympathetic activity. This study assessed both parasympathetic and sympathetic control and the potential influence of cardiorespiratory fitness and body mass index (BMI) on autonomic function in a sample of young adults with and without MDD. Cardiac autonomic balance, which reflects both parasympathetic and sympathetic activity, significantly predicted current MDD, even after controlling for cardiorespiratory fitness and BMI. Substantial variation in autonomic control remained that was not captured by the traditional model of reciprocal autonomic balance.